AKTIVITAS ANTIOKSIDAN DAN KADAR TOTAL FENOL MAKROALGA PERAIRAN TANJUNG BENOA, BALI - Jannah Sofi Yanty; I Wayan Karta (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Purpose : The purpose of this study was to determine antioxidant activity of macroalgae in Tanjung Benoa, Bali, Method : In this research, the antioxidant activity of macroalgae in Tanjung Benoa, Bali, will be tested using the DPPH method. Total phenolic test / TPC (Total Phenolic Content) test was also carried out on macroalgae samples using the Folin-Ciocalteau method. TPC value is expressed as the equivalent of mg gallic acid (GAE)/g dry weight of the sample. Result: Samples obtained at the time of sampling were 10 macroalgae samples consisting of 5 red macroalgae (rhodophyta), 4 green macroalgae (chlorophyta) and 1 brown macroalgae (phaeophyta). The results of the antioxidant analysis showed that the 4 macroalgae that had the greatest percentage of inhibition were the macroalgae Chondrus crispus, Sargassum sp., Gracilaria sp and Acrosorium sp.1. The results of total phenol analysis showed that the highest levels of total phenol were found in macroalgae Sargassum sp., Gracilaria sp. and Acrosorium sp. 1. Conclucion : Total phenolic content of most of the macroalgae samples had a positive correlation with antioxidant potential.Keywords: macroalgae, antioxidants, total phenols, DPPH, Tanjung Benoa